Effective and democratic long-term radioactive waste governance: Lessons from Europe - Romy Dekker; Rinie van Est (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Radioactive waste management (RWM) presents a complex long-term governance challenge due to its decades-to-centuries-long timeframes and associated uncertainties. In response to societal resistance to top-down governance approaches, most European countries have adopted new strategies to make RWM governance more democratic and effective. This article explores how four interlinked key areas of long-term governance – decision-making, public participation, knowledge, and financing – are shaped by various European countries through interconnected procedures, principles, and institutions. It identifies nine lessons for democratic and effective long-term RWM governance, concluding that a stepwise, participatory approach is a promising strategy to deal with the uncertainties and democratic deficits inherent in long-term issues. However, realizing this potential requires a continuous search for adequate procedures, principles, and institutions.